Bulk heterojunction organic solar cell fabricated on SiO2 diffraction gratings - Wang, Yi. (2009)
Nowadays, conventional energy sources, namely fossil fuel, are being consumed at an alarming rate. This drives the electric power to a much higher price, and generates environmental issues, particularly, climate change. One possible solution to the energy crisis is to utilize solar energy which is free and sufficient in amount. Organic solar cell has been researched and studied in recent decades, especially in the last ten years due to their intrinsic low cost. It has attracted scientific and economic interest triggered by a rapid increase in power conversion efficiencies. New materials have been introduced, and more sophisticated device structure has been developed to improve the device properties further. Although the efficiencies of organic solar cell devices are still lower than those achieved by their inorganic counterparts (η = 10 – 20%), the relatively cheap process, ease in production and flexible form factor give clear advantage to organic solar cells in some wide applications. At present, bulk heterojunction organic solar cells are empirically fabricated on indium thin oxide coated glass, which is commercially available. In this work, a SiO2 substrate with patterned SiO2 gratings is used as substrate to fabricate bulk heterojunction organic solar cell. Furthermore, great modifications are made to the device structure, and the fabrication process is in turn, changed from conventional steps. The novel structure designed possesses several advantages over the conventional ones. However, it also imposes difficulties in the fabrication steps. This project aims to study the current organic solar cell technology, and based on the comprehensive understanding, design a novel structure of bulk heterojunction organic solar cell that is theoretically applicable. The second task is to solve the fabrication difficulties and develop the designed structure in cleanroom laboratory, hence, to prove that the new structure is practically achievable. Lastly, the device is tested under solar simulator to see whether it undergoes predicted photovoltaic properties.